Natascha Sojc (ed.), Akragas. Current Issues in the Archaeology of a Sicilian Polis - Bergemann, Johannes (Journal of Greek Archaeology, 2021)
In recent years research regarding Agrigento was the most intensive of all the ancient places in Sicily. This resulted from the stimulating charisma of the Archaeological Park and its administration, as well as the Soprintendenza. Italian and international teams examined the architecture, urban planning, the newly found theatre, and the Roman and late antique city. The Park and the Archaeological Museum have exhibited the results in museums for the public. In addition, archaeological surveys examined the ancient city and its hinterland. Natascha Sojc, first affiliated to Leiden University and now to the University of Augsburg, carried out archaeological and geophysical surveys in the suburban sanctuary of S. Anna. This collaborative effort resulted in the present volume that is based on a colloquium.